Association between micronutrients and myopia in American adolescents: evidence from the 2003–2006 National Health and Nutrition Examination Survey - Xiao, Kunhong; Chen, Ruiye; Lin, Rong; Hu, Wenyi; Liu, Jiahao; Yusufu, Mayinuer; Huang, Yan; Li, Li (Frontiers in Nutrition, 2024)
Purpose: To investigate the associations between circulating micronutrients (vitamins A, C, D, E, and carotenoids) and the risk of myopia. Methods: A total of 1,620 adolescents from the 2003-2006 National Health and Nutrition Examination Survey (NHANES) were included. Logistic regression was used to analyze the associations of micronutrients with myopia and high myopia. Restricted cubic spline analysis was employed to assess the potential nonlinear relationships. Results: Among the 1,620 adolescents, 549 were diagnosed with myopia. After adjusting for multiple covariates, only cis-β-carotene was significantly associated with the risk of myopia (OR 1.19, 95% CI 1.03-1.39) and high myopia (OR 1.44, 95% CI 1.03-2.03). No significant associations were found between vitamins A, D, E, C, α-carotene, trans-β-carotene, lutein zeaxanthin, and myopia. No nonlinear relationships were observed between any of the micronutrients and myopia. Conclusion: Cis-β-carotene is significantly associated with an increased risk of myopia and high myopia. Further research is needed to understand the underlying mechanisms and potential impact of cis-β-carotene on ocular health